2014
DOI: 10.1177/1759091414551782
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Cortical and White Matter Traumatic Brain Injury Models Reveals Differential Effects in the Subventricular Zone and Divergent Sonic Hedgehog Signaling Pathways in Neuroblasts and Oligodendrocyte Progenitors

Abstract: The regenerative capacity of the central nervous system must be optimized to promote repair following traumatic brain injury (TBI) and may differ with the site and form of damage. Sonic hedgehog (Shh) maintains neural stem cells and promotes oligodendrogenesis. We examined whether Shh signaling contributes to neuroblast (doublecortin) or oligodendrocyte progenitor (neural/glial antigen 2 [NG2]) responses in two distinct TBI models. Shh-responsive cells were heritably labeled in vivo using Gli1-CreERT2;R26-YFP … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
60
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(65 citation statements)
references
References 32 publications
4
60
1
Order By: Relevance
“…It has been shown that Shh signaling influences proliferation of several cell types following injuries (Cheng et al, ; He et al, ; Sims et al, ); however, we did not find any impact of this signaling pathway on the proliferation of Tomato+ NG2 cells after FCI. These results correspond with previously shown importance of Shh signaling in the proliferation of many cell types except Olig2‐positive NG2 cells after injury (Mierzwa et al, ; Pitter et al, ). Several studies demonstrated that Shh increases the number of proliferating astrocytes after CNS pathologies (Amankulor et al, ; Sirko et al, ); nevertheless, this phenomenon could also be explained by an increased number of astrocytes per mm 2 , which are derived from NG2 cells due to the activation of Shh signaling pathway.…”
Section: Discussionsupporting
confidence: 92%
“…It has been shown that Shh signaling influences proliferation of several cell types following injuries (Cheng et al, ; He et al, ; Sims et al, ); however, we did not find any impact of this signaling pathway on the proliferation of Tomato+ NG2 cells after FCI. These results correspond with previously shown importance of Shh signaling in the proliferation of many cell types except Olig2‐positive NG2 cells after injury (Mierzwa et al, ; Pitter et al, ). Several studies demonstrated that Shh increases the number of proliferating astrocytes after CNS pathologies (Amankulor et al, ; Sirko et al, ); nevertheless, this phenomenon could also be explained by an increased number of astrocytes per mm 2 , which are derived from NG2 cells due to the activation of Shh signaling pathway.…”
Section: Discussionsupporting
confidence: 92%
“…Other authors supported this hypothesis as well [42][43][44][45][46] and we considerate that those results cannot be transferred to human beings.…”
Section: Some Sportsmen Presenting Amyotrophic Lateral Sclerosissupporting
confidence: 77%
“…46–48 Our previous studies in the s-mTBI model found that NG2 cell density increased in the corpus callosum and cortex during the initial weeks post-injury with less of an elevation by 6 weeks post-injury. 20,49 In r-mTBI mice, the NG2 cell population was not affected in the corpus callosum or cortex in the post-imaging 6-week cohort (Fig. 6C,D,F,H).…”
Section: Resultsmentioning
confidence: 92%